Lithic production sequences in the southern Argentinian Puna during the initial middle Holocene: Quarry-workshop characterization in the mid-course of the Ilanco River - Funes Coronel, Jorge Alejandro (2013)
The study adds new information to the existing data on the spatial distribution of lithic raw material sources suitable for flintknapping in the microregion of Antofagasta de la Sierra (Catamarca Province), in the southern Argentinian Puna. The analysis aims at a physical and functional characterization of a large volcanic rock source detected in 1999 in the Ilanco River at w3750 m asl. It is composed entirely of basalt, a very good rock type for flintknapping. Use was recorded at various archaeological sites in the area, from the early Holocene. Numerous cores, nodular flakes and sub-products of flintknapping episodes from prehispanic occupations were registered on the surface. The archaeological site Peñas de la Cruz 1.1 (PCz1.1; 3665 m asl) is nearby, a rockshelter that shows the predominant use of this raw material in a lithic production system particularly oriented towards the manufacturing of bifaces and lanceolate projectile points. Context dates to the initial middle Holocene, between ca. 7910e7270 BP.